Regional Differences in Various Risk Factors for Postpartum Depression: Applying Mixed Models to the PRAMS Dataset - Gifford, Janace J.; Pluchino, Jenna R.; Della Valle, Rebecca; Schwarz, Jaclyn M. (Frontiers in Global Women's Health, 2021)
Purpose: The purpose of this study was to assess the association between various risk factors with postpartum depression severity using a large dataset that included variables such as previous mental health status, social factors, societal factors, health care access, and other state-wide or region-specific variables. Methods: We obtained the most recently available (2016–2017) dataset from the Pregnancy Risk Assessment Monitoring System (PRAMS), which is a dataset compiled by the Centers for Disease Control (CDC) that collects state-specific, population-based data on maternal attitudes and experiences before, during, and shortly after pregnancy from over 73,000 women in 39 states. We utilized a hierarchical linear model to analyze the data across various levels, with a symptom severity scale (0–8) as the dependent variable. Results: Of the 21 variables included in the final model, nine variables were statistically significant predictors of symptom severity. Statistically significant predictors of increased postpartum depression symptom severity included previous depression diagnosis and depression symptoms during pregnancy, baby not residing with mother, unintentional pregnancy, women with less than a high school degree and more than a college degree, Women Infants Children (WIC) enrollment, and married women. In contrast to these other factors, attendance at a postpartum follow up appointment was associated with significantly increased symptom severity. Age revealed an inverted curve in predicting postpartum symptom severity. Conclusions: There was no significant difference in symptom severity scores across the 39 participating states. Most notably, postpartum depression symptom severity was associated with previous depression diagnosis and previous symptom severity, but our results also reveal novel social and education factors that contribute to the support and well-being of the mother and child.